Characterization of Degradable Plastics from Sago and Breadfruit Starch-Based with Addition of Zinc Oxide (ZnO) Catalyst and Polyvinyl Alcohol (PVA) - Medyan Riza; Rozanna Dewi; Novi Sylvia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Degradable plastic can be used as a substitute for commercial plastic. Degradable plastic made from starch with zinc oxide (ZnO) catalyst and polyvinyl alcohol (PVA) has biodegradable properties. This research used sago starch, breadfruit starch, ZnO catalyst, and PVA as additives to strengthen the mechanical properties of degradable plastic. The research methodology encompassed several stages, including the preparation of sago and breadfruit starch, the synthesis of degradable plastic, and the subsequent evaluation of its characteristics. Various concentrations of ZnO and PVA catalysts (10%, 20%, 30%, and 40%) were employed in this study. Mechanical characteristic test for degradable plastic showed that the tensile strength test for sago starch-based plastic with 40% ZnO catalyst and PVA was 2.31–3.96 MPa, while for breadfruit starch-based degradable plastic was 2.88–3.20 MPa. FTIR analysis revealed that the compound constituents of degradable plastics exhibit hydrophilic properties and readily interact with water, making them susceptible to natural degradation in soil. Furthermore, the thermal characteristics were examined using DSC, which indicated that sago starch-based degradable plastic (with ZnO 40% and PVA 40%) exhibited a thermogram peak at a temperature of 137.15°C, while the breadfruit starch-based plastic displayed a peak at 136.97°C. In terms of water absorption, the swelling index for sago starch-based plastic ranged from 18.35% to 65.26%, whereas for breadfruit starch-based plastic, it ranged from 19.91% to 64.06%. Notably, the lowest water absorption levels were observed at a ZnO concentration of 40% and a PVA concentration of 10%. The higher the PVA concentration, the more water was absorbed due to the hydrophilic nature of PVA, but the higher the ZnO concentration, the lower the water absorption. Degradation of plastics sago and breadfruit starch occurred for 20-28 days and by ASTM D-20.96 (degradable plastics should be decomposed before 180 days). The higher the concentration of ZnO catalyst added to bioplastics, the longer the degradation time, while the higher the PVA content, the faster the degradation time.